Silane-modified carbon fibers reinforced cyanate ester/benzoxazine resin composites: Morphological, mechanical and thermal degradation properties. (April 2018) - Zegaoui, Abdeldjalil; Derradji, Mehdi; Ma, Ruikun; Cai, Wan-an; Medjahed, Aboubakr; Liu, Wen-ben; Qadeer Dayo, Abdul; Wang, Jun
Abstract: In this paper, various concentrations of silane treated carbon fibers (TCFs) were incorporated within cyanate ester/benzoxazine resin to demonstrate their effects on the morphological, mechanical, thermal decomposition properties of the composites. Mechanical test inferred the distinctive improvements in the values of the flexural strength and modulus. The glass transition temperature ( T g ) determined from the DSC measurements were appreciably higher than those of the unfilled blend. TGA results showed an improved in the thermal stability in terms of the T 5%, T 10%, Y c, T HRI and LOI for all composites. For instance, the T 5%, T 10%, Y c, T HRI and LOI were respectively 345.1 °C, 391.8 °C, 50.1%, 217.1 °C and 37.5% for the composites with 20 wt% of the TCFs. The thermal degradation was assessed by evaluating the variation of the activation energy ( E ac ) of the composites by using three kinetic models, namely Horowitz and Metzger, Coat and Redfern, and Broido models. It was found that the E ac greatly increased and further reflected the improvement in the thermal stability of the composites. This could be attributed the unique characteristics of the TCFs that possibly resulted in effective physical barrier effects against thermal degradation, thereby leading to the amelioration of the thermal properties. Highlights: CE/BOZ resin blend was reinforced by various amounts of silane modified CFs. SEM confirms the good adhesion and dispersion of TCFs inside the resin. F S and F m reached the value of 176.8 MPa and 5.79 GPa at the 20 wt% TCFs. Thermal properties were gradually increased upon increasing the fiber loadings. Evaluation of activation energy values further confirmed the enhancements in the thermal stabilities.